2020
DOI: 10.1177/0047287520961175
|View full text |Cite
|
Sign up to set email alerts
|

Why Are International Visitors More Satisfied with the Tourism Experience? The Role of Hedonic Value, Escapism, and Psychic Distance

Abstract: Previous studies have consistently observed that international visitors are more satisfied with the tourism experience than their domestic counterparts. To date, however, no study has provided empirical evidence of the mechanism that could explain this phenomenon. Building on the experiential paradigm, we conducted two empirical studies (a field study and an online experiment) showing that the reason foreign (vs. domestic) visitors exhibit higher levels of satisfaction lies in the greater hedonic value that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 77 publications
3
42
0
Order By: Relevance
“…According to Hirschman and Holbrook (1982) and Holbrook (1996) , emotional arousal is the basis for tourists' decision-making. That is, the emotional and hedonic values that tourists derive from travel experience profoundly influence tourists' satisfaction (Ponsignon et al, 2020) and continued usage or revisit intentions (Ozturk et al, 2016;Petrick et al, 2001). Food consumption may be deserved to receive more attention in preparation for the anticipated return to pre-pandemic standard if destinations recover from the slump (Vaishar and S tastn a, 2020;Wen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hirschman and Holbrook (1982) and Holbrook (1996) , emotional arousal is the basis for tourists' decision-making. That is, the emotional and hedonic values that tourists derive from travel experience profoundly influence tourists' satisfaction (Ponsignon et al, 2020) and continued usage or revisit intentions (Ozturk et al, 2016;Petrick et al, 2001). Food consumption may be deserved to receive more attention in preparation for the anticipated return to pre-pandemic standard if destinations recover from the slump (Vaishar and S tastn a, 2020;Wen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to Hirschman and Holbrook (1982) and Holbrook (1996) , emotional arousal is the basis for tourists' decision-making. That is, the emotional and hedonic values that tourists derive from travel experience profoundly influence tourists' satisfaction (Ponsignon et al. , 2020) and continued usage or revisit intentions (Ozturk et al.…”
Section: Introductionmentioning
confidence: 99%
“…We used an independent sample t-test to test hypotheses 1 and 2. We computed the mean scores of the goal commitment scale and goal-directed behaviors scale, respectively, and used the mean values in the independent samples t test (Confente and Scarpi 2020;Hair et al 2009;Ponsignon, Lunardo, and Michrafy 2020). The result showed that goal-directed behaviors of tourism goal disclosure were significantly higher than those of tourism goal nondisclosure (M disclosure = 5.96, SD = 0.49, vs. M nondisclosure = 5.31, SD = 1.31, t = 3.38, p < 0.01; see Figure 2); thus, hypothesis 1 was supported.…”
Section: Main Experimentsmentioning
confidence: 99%
“…In particular, cosmopolitans are considered as a particularly attractive target group (Riefler et al 2012). Escapists, by desiring experiences different from everyday life, can exhibit a strong travel motivation (Ponsignon, Lunardo, and Michrafy 2020). Individuals' cognitive thinking style, by reflecting the mode of information processing, captures a relevant decision-making facet of tourists (Hong and Desai 2020).…”
Section: Moderator Variables On the Ci-mi-r Frameworkmentioning
confidence: 99%
“…Escapism is a travel motivation that drives people to escape from their daily life and return to their routines after experiencing the extraordinary (Labrecque, Krishen, and Grzeskowiak 2011;Loureiro 2014). This kind of experience involves tourists who travel to destinations "worthy of their time," which are different from those most people are familiar with (e.g., long-distance travels, cyberspace; Pine and Gilmore 1998;Ponsignon, Lunardo, and Michrafy 2020).…”
Section: Moderator Variables On the Ci-mi-r Frameworkmentioning
confidence: 99%